Outcomes following hip and quadriceps strengthening exercises for patellofemoral syndrome: A systematic review and meta-analysis - Bisi-Balogun, A.; Torlak, F. (Sports, 2015)
There is growing evidence to support change in the rehabilitation strategy of patellofemoral pain syndrome (PFPS) from traditional quadriceps strengthening exercises to inclusion of hip musculature strengthening in individuals with PFPS. Several studies have evaluated effects of quadriceps and hip musculature strengthening on PFPS with varying outcomes on pain and function. This systematic review and meta-analysis aims to synthesize outcomes of pain and function post-intervention and at follow-up to determine whether outcomes vary depending on the exercise strategy in both the short and long term. Electronic databases including MEDLINE, EMBASE, CINAHL, Web of Science, PubMed, Pedro database, Proquest, Science direct, and EBscoHost databases were searched for randomized control trials published between 1st of January 2005 and 31st of June 2015, comparing the outcomes of pain and function following quadriceps strengthening and hip musculature strengthening exercises in patients with PFPS. Two independent reviewers assessed each paper for inclusion and quality. Means and SDs were extracted from each included study to allow effect size calculations and comparison of results. Six randomized control trials met the inclusion criteria. Limited to moderate evidence indicates that hip abductor strengthening was associated with significantly lower pain post-intervention (SMD -0.88, -1.28 to -0.47 95% CI), and at 12 months (SMD -3.10, -3.71 to -2.50 95% CI) with large effect sizes (greater than 0.80) compared to quadriceps strengthening. Our findings suggest that incorporating hip musculature strengthening in management of PFPS tailored to individual ability will improve short-term and long-term outcomes of rehabilitation. Further research evaluating the effects of quadriceps and hip abductors strengthening focusing on reduction in anterior knee pain and improvement in function in management of PFPS is needed.